2007
DOI: 10.1016/j.juro.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of 3 Novel DNA Methylation Markers of Prostate Cancer Prognosis

Abstract: We report that methylation of the 3 novel markers GPR7, ABHD9 and Chr3-EST is significantly associated with prostate cancer prognosis. Incorporation of these methylation markers into clinical practice will result in more accurate prediction of which patients are likely to experience PSA recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 16 publications
0
61
0
Order By: Relevance
“…Patient clinical characteristics and methods used to isolate DNA have been reported (12). With a median of 60.2 months follow up, 14 patients had biochemical evidence of recurrent disease, whereas 22 did not.…”
Section: Clinical Profile Of Casesmentioning
confidence: 99%
“…Patient clinical characteristics and methods used to isolate DNA have been reported (12). With a median of 60.2 months follow up, 14 patients had biochemical evidence of recurrent disease, whereas 22 did not.…”
Section: Clinical Profile Of Casesmentioning
confidence: 99%
“…For example, ABHD9 is hypermethylated in human malignant melanomas [59], gastric cancers [60], adenoid cystic carcinomas of salivary glands [61], and colorectal carcinomas [62]. Hypermethylation of ABHD9 has been associated with prostate cancer recurrence [63, 64], and AHBD9 expression is also deregulated in some B cell malignancies [65]. Based on these studies, it is possible that ABHD9 substrates may contribute to cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…In a methylation oligonucleotide microarray study of 304 frozen prostatectomy samples, Cottrell et al previously reported that promoter region methylation of ABHD9 was significantly increased in patients who experienced early PSA recurrence versus non-recurrent men (Bonferroni-adjusted P < 0.05) (10). The significance of the result with respect to biochemical recurrence was then confirmed in a cohort of 605 RP patients (12).…”
Section: Discussionmentioning
confidence: 99%